Biochemical, physiological, and yield responses of lady’s finger (Abelmoschus esculentus L.) grown on varying ratios of municipal solid waste vermicompost - Vaibhav Srivastava; Sanjay Kumar Gupta; Pooja Singh; Bhavisha Sharma; Rajeev Pratap Singh (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose In the present study, effect of earthworm-processed MSW was seen on biochemical, physiological, and yield responses of Abelmoschus esculentus L. Methods Plants were grown on different amendment ratios of municipal solid waste vermicompost (MSWVC). Pot experiments were conducted by mixing MSWVC at 0, 20, 40, 60, 80, and 100% ratios to the agricultural soil. Results An increase in photosynthetic rate and stomatal conductance of plants grown at 20 and 40% MSWVC amendment ratios was observed. Total chlorophyll, carotenoid, and protein contents also increased significantly in 20, 40, and 60% amendment ratios at 65 days after germination (DAG). Likewise, proline, peroxidase, and lipid peroxidation increased with increasing levels of MSWVC at both 45 and 65 DAG. Conclusion The study suggests that MSWVC could be used as organic amendment in soil depicted by good yield and antioxidative response of lady’s finger (A. esculentus) at different amendments of MSWVC (up to 60% w/w ratios). Furthermore, agricultural utilization of MSWVC will help in managing dreadful effects of the burgeoning amount of organic solid waste.